Implementasi Aplikasi Human Resource Management System (HRMS) Berbasis Web Dan Android Menggunakan Metodologi Agile - Titih Aji Kurniawan; Agung Triayudi; Sari Ningsih (JURIKOM (Jurnal Riset Komputer), 2023)
The attendance system at PT Garda Paksi Nusantara is still manual and based on Microsoft Excel and there is no Android-based employee attendance system yet. What is PT Garda Paksi Nusantara's need for web and android-based Human Resource Management System (HRMS) applications in order to keep pace with developments in information and communication technology. This research uses observation, interview, and literature study methods. The development method is carried out using the Agile Method with the SCRUM method. The results of this study created a web-based and Android-based Human Resources Management Systems application for PT Garda Paksi Nusantara and has been tested with blackbox testing 9 (nine) times. The existence of a Web-based and Android-based Human Resource Management System (HRMS) application utilizes internet facilities which are expected to be a tool to facilitate the presentation of information and data processing can be carried out quickly and precisely, especially for HRD and company employees, so that HRD and employees are expected to be able to use and utilize internet facilities in terms of data information and data processing so as to improve administrative systems and work effectiveness better. For future researchers, it is expected to add a fingerprint attendance system (finger print) and face detection to produce accurate output. The application of this system is expected to maintain and improve employee work discipline.